2009
DOI: 10.1038/cdd.2009.42
|View full text |Cite
|
Sign up to set email alerts
|

Rocaglamide sensitizes leukemic T cells to activation-induced cell death by differential regulation of CD95L and c-FLIP expression

Abstract: Drugs with tumor selectivity may have an important benefit in chemotherapies. We have previously shown that Rocaglamide(s), derived from the medicinal plant Aglaia, kills various leukemic cells through the mitochondrial apoptosis pathway with only minor toxicities to normal lymphocytes. Here, we show further that Rocaglamide preferentially promotes activation-induced cell death in malignant T cells by differential regulation of c-FLIP and CD95L expression. Rocaglamide enhances and also prolongs activation-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 39 publications
5
50
0
Order By: Relevance
“…9 Roc has also been shown to inhibit tumor growth in vivo in mouse tumor models with no toxicity to the liver evaluated by glutamate pyruvate transaminase activity and also no body weight loss. 8,11,15,42 In this study, we show that Roc-A could induce an ATM/ATR-response in many types of cancer cell lines (Fig. 5h).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…9 Roc has also been shown to inhibit tumor growth in vivo in mouse tumor models with no toxicity to the liver evaluated by glutamate pyruvate transaminase activity and also no body weight loss. 8,11,15,42 In this study, we show that Roc-A could induce an ATM/ATR-response in many types of cancer cell lines (Fig. 5h).…”
Section: Discussionsupporting
confidence: 53%
“…9,15 However, whether Roc-A also preferentially inhibits cell-cycle progression in tumor cells has not been examined. To investigate this question peripheral blood T lymphocytes were isolated from healthy donors.…”
Section: Roc-a Inhibits G1-s Transition In Malignant But Not In Normamentioning
confidence: 99%
“…Recently, we have shown that Roc suppresses activation-induced expression of c-FLIP in leukemic T cells at the transcriptional level by downregulation of NF-AT activity. 27 In that study, we noticed that the basal level of c-FLIP expression (without activation) was also reduced upon Roc treatment. Thus, we asked whether Roc can sensitize ATL cells to receptor-mediated apoptosis through suppression of c-FLIP expression.…”
Section: Resultsmentioning
confidence: 83%
“…26 Recently, in vitro and an in vivo mouse T-cell leukemia model, we showed high toxicity to tumor cells and only minor toxicity towards normal cells, e.g., activated T cells. 26,27 Toxicity and cell death is mediated through suppression of c-FLIP expression at the transcriptional level by blocking NF-AT activation. 27 Here, we further investigated whether Roc inhibits c-FLIP expression by additional mechanisms and whether it can be used as a sensitizer of receptor-mediated apoptosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation